The Development of Liveworksheets-Assisted Problem-Based Learning Teaching Materials to Improve Students’ Mathematical Communication Skills - Rusmiati, Mia; Minarti, Eva Dwi; Maya, Rippi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
This study aims to measure the level of validity, practicality and effectiveness of Problem Based Learning social arithmetic teaching materials assisted by Liveworksheets. This study uses the Research and Development (R&D) method of Sugiyono's development model which consists of 10 stages which are limited to step 7, namely: potential and problems, data collection, product design, design validation, design revision, product trial, and product revision. The research subjects were: a VII grade math teacher, 10 VIII grade students, and 30 VII grade students. Instruments in this study include: interview sheets, validation sheets, student response questionnaires, and mathematical communication skills tests. Data processing techniques in the form of quantitative data analysis include validity analysis, practicality analysis, and effectiveness analysis of test results. The results of this study that LKPD teaching materials have met the eligibility criteria. This is because based on the results of the validation of experts who get a score of 80% which is considered valid. In the limited product trial, a score of 81% was obtained in the very practical category. As well as extensive product trials obtained a score of 85% with a very practical category. Then during the effectiveness test, it got a score of 80% with the effective category. Thus teaching materials in the form of learner worksheet are suitable for use in the learning process.